NPY regulates catecholamine secretion from human adrenal chromaffin cells - Cavadas, Cláudia (2001)
The aim of the present work was to find out whether NPY synthesized in human adrenal chromaffin cells controls in an autocrine/paracrine fashion the release of catecholamines by these cells. Accordingly, the constitutive and regulated release of both NPY and catecholamines was measured simultaneously in cultured human chromaffin cells. In addition, by using both RT-PCR and a combination of specific agonists and antagonists, we characterized the expression of NPY receptors on these cells as well as their pharmacology. Our results were as follows. 1) Human chromaffin cells constitutively secrete NPY. 2) Nicotine elicits a rapid increase in the release of both catecholamines and NPY; this release of NPY is more sustained than that of catecholamines. 3) RT-PCR shows expression of Y1, Y2, Y4, and Y5 receptor mRNA by chromaffin cells; these receptors are functional, as various receptor specific agonists elicit an increase in intracellular calcium. 4) Peptide YY, in contrast to NPY, is not able to stimulate the release of catecholamines. This finding was corroborated by the observation that no receptor-specific antagonists were able to reduce constitutive catecholamine release, whereas an NPY-immunoneutralizing antibody markedly attenuated the secretion. Taken together, these data suggest that NPY originating from the adrenal medulla locally enhances the secretion of catecholamines, presumably by acting via the putative y3 receptor